Long‐lived murine osteocytes are embodied by craniofacial skeleton in young and old animals whereas they decrease in number in postcranial skeletons at older ages. (27th July 2018) - Stigler, Robert G.; Becker, Kathrin; Kloss, Frank R.; Gassner, Robert; Lepperdinger, Günter
Abstract : Background: Osteocytes are engaged in life‐enduring processes such as bone remodelling, fracture healing or osseointegration of implants. Over age, ossification processes and regenerative capacity can greatly differ in mandible and femur. Objective: Mesenchymal stem cells from cranial and postcranial bones are of different embryologic origin. This may be the reason why the regenerative capacity differs between cranial and postcranial bones in old patients. It was hypothesised that different ageing patterns, reflected by osteocyte density, lacunar density and osteoid formation, exist between murine mandibles and femurs. Material and methods: Mandible and femur of young (4 months) and old (34‐36 months old) male C57Bl/6 mice were histologically investigated to determine the number of lacunae occupied with osteocytes. Osteoid formation was revealed by Masson‐Goldner staining, and the spatial distribution of BMP‐2 synthesis was examined. Results: Over lifetime, the number of lacunae occupied with osteocytes only showed a modest decrease in mandibular bone (old 85.63%/young 91.12%) while greatly diverging in the femur (old 55.99%/young 93.28%). In equal measure, old femur exhibited less osteoid formation and decreased BMP‐2 expression. Conclusion: Tissue‐specific conduct of bone ageing is moulded by osteocytic activities, which was found to vary between postcranial and craniofacial skeleton. The latter harbours long‐lived osteocytes also in old animals which assures lifelong bone integrity. Preliminary concurring findings from a human cadaver, also presented in this contribution, provided a rationale for recommending the translatability to humans.